Identity Narratives on TikTok: Analysis of the Forbes 2024 Awards - Barron San Blas, Patricia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The research examines the influence exerted by TikTokers featured in the Forbes 2024 list on the construction of individual and collective identities in cyberspace. Using a purposefully developed rubric, the research seeks to qualitatively explore the self-representation strategies and performative practices of the nominated profiles (n=34). The findings reveal how these practices shape discourses, generate trends, reinforce stereotypes, and configure aspirations that affect audiences. In addition, the conclusions emphasize the role of content creators in shaping digital narratives, highlighting the complex interactions between individual influence –along with social impact– and the construction of personal brand.